PENGARUH METODE PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS X SMA PGRI 4 DENPASAR - Putu Dessy Fridayanthi; Ida Ayu Agung Ekasriadi (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Problem based learning is a learning method that demands full student activity in order to solve any problems faced by students independently by constructing their knowledge and understanding. The purpose of this study was to determine the effect of the problem-based learning method on the results of learning Indonesian in class X SMA PGRI 4 Denpasar. This type of research is a quasi-experimental quantitative (quasi-experimental design). The research subjects were students of class X MIPA at SMA PGRI 4 Denpasar for the 2022/2023 academic year. The samples in this study were 36 students in class X MIPA 1 as an experimental class and 35 in class X MIPA 2 as a control class at SMA PGRI 4 Denpasar. In this study using data collection techniques, namely by observation and tests. The analysis technique used is the t-test formula. From the research results obtained tcount = 3.835 while ttable = 2.024 this means tcount > ttable, then Ha is accepted which states that there is an influence of the problem based learning method on the results of Indonesian language learning for class X students. So there is an influence of the problem based learning method on the results learn Indonesian for class X SMA PGRI 4 Denpasar for the 2022/2023 academic year.